3-Dimensional Facial Analysis—Facing Precision Public Health - Baynam, Gareth; Bauskis, Alicia; Pachter, Nicholas; Schofield, Lyn; Verhoef, Hedwig; Palmer, Richard L.; Kung, Stefanie; Helmholz, Petra; Ridout, Michael; Walker, Caroline E.; Hawkins, Anne; Goldblatt, Jack; et al. (Frontiers in Public Health, 2017)
Precision public health is a new field driven by technological advances that enable more precise descriptions and analyses of individuals and population groups, with a view to improving the overall health of populations. This promises to lead to more precise clinical and public health practices, across the continuum of prevention, screening, diagnosis and treatment. A phenotype is the set of observable characteristics of an individual resulting from the interaction of a genotype with the environment. Precision (deep) phenotyping, applies innovative technologies to exhaustively and more precisely examine the discrete components of a phenotype, and goes beyond the information usually included in medical charts. This form of phenotyping is a critical component of more precise diagnostic capability and 3D facial analysis (3DFA) is a key technological enabler in this domain. In this paper we examine the potential of 3DFA as a public health tool, by viewing it against the 10 essential public health services of the ‘public health wheel’, developed by the US Centers for Disease Control. This provides an illustrative framework to gauge current and emergent applications of genomic technologies for implementing precision public health.